Mapping sweetness preference across the lifespan for culturally different societies. (August 2018) - Pellegrino, Robert; Sorokowska, Agnieszka; Marczak, Michalina; Niemczyk, Agnieszka; Butovskaya, Marina; Huanca, Tomas; Sorokowski, Piotr
Abstract: The preference of sweetened foods can be influenced by a variety of biological, psychological, sociological, and environmental factors. In this study, we focused on differences across three distinct societies: 1) a modern society (i.e., Polish people, n = 199), 2) forager-horticulturalists from Amazon/Bolivia (Tsimane', n = 138), and 3) traditional hunter-gatherers from Tanzania (Hadza, n = 81). To measure sweet preference, participants were asked to drink three cups containing slightly acidic solutions (pH = 2.79) varying in sucrose concentration (w/v; 0%, 25%, 67%). Only 5% of the Polish participants chose the sweetest cup as their favorite, while this cup was chosen by 74% of the Hadza and 53% of the Tsimane' participants. Further, age was an inversely related to sweet preference for Polish participants; however, age did not predict preferences for both Tsimane' and Hadza tribes. We discuss our findings in the context of environmental and cultural differences between the participating populations. Highlights: Both Hadza and Tsimane' societies liked sweetness more than the Polish society, with Hadza having the highest preference for sweets. Unlike most western societies, Hadza and Tsimane' show no decline in sweet preference with age. Maintenance of energy expenditure with highly sweet foods for some non-western societies may explain higher sweet preference.